Pengaruh Kualitas Produk dan Persepsi Harga Terhadap Keputusan Pembelian Pada Konsumen Ali Jaya Meubel - Hendi ali permana; Rita Tri Yusnita; Nita Fauziah Oktaviani (J-CEKI : Jurnal Cendekia Ilmiah, 2023)
This study aims to determine the effect of product quality and price perceptions on purchasing decisions (survey on consumers of Ali Jaya Meubel). The method used in this study is causality through a survey approach. With a research sample of 100 consumers of Ali Jaya Furniture. The data used is using primary data. The analytical tool used in this study is multiple regression using SPSS 26.0. The results of the study show that simultaniosly product quality and price perceptions have a significant influence on purchasing decisions at Ali Jaya Furniture. Partially, product quality and price perception has a significant influence on purchasing decisions at Ali Jaya Furniture.